2020
DOI: 10.5607/en20040
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hand Dexterity Function in a Non-human Primate Model with Chronic Parkinson’s Disease

Abstract: Symptoms of Parkinson' s disease (PD) caused by loss of dopaminergic neurons are accompanied by movement disorders, including tremors, rigidity, bradykinesia, and akinesia. Non-human primate (NHP) models with PD play an essential role in the analysis of PD pathophysiology and behavior symptoms. As impairments of hand dexterity function can affect activities of daily living in patients with PD, research on hand dexterity function in NHP models with chronic PD is essential. Traditional rating scales previously u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The interventional radiology method employed in this study was performed as reported in our previous studies [ 17 , 30 33 ]. All monkeys were anesthetized with ketamine (5 mg/kg, I. M, Yuhan, Seoul, South Korea) and maintained with isoflurane (2%, Hana Pharmacy, Hwaseong, South Korea).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interventional radiology method employed in this study was performed as reported in our previous studies [ 17 , 30 33 ]. All monkeys were anesthetized with ketamine (5 mg/kg, I. M, Yuhan, Seoul, South Korea) and maintained with isoflurane (2%, Hana Pharmacy, Hwaseong, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…All MRI examinations were conducted using a Philips 3T Achieva scanner (Philips Medical System, Best, Netherlands) with a 32-channel head coil. Monkeys were comfortably restricted in a supine position in a custom-made bed holder during MRI scans [ 17 , 32 , 33 ]. Inhaled CO 2 , O 2 saturation, pulse, respiration rate, and body temperature were continuously monitored.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations